Potential Research Tool of Stem Cells from Human Exfoliated Deciduous Teeth: Lentiviral Bmi-1 Immortalization with EGFP Marker - Siqi Yao; Lingping Tan; Huan Chen; Xiaojun Huang; Wei Zhao; Yan Wang (Stem Cells International)
Stem cells from human exfoliated deciduous teeth (SHED) are a favourable source for tissue engineering, for its great proliferative capacity and the ease of collection. However, the transplantation of stem cells and the study of stem cell-based tissue engineering require massive stem cells. After long-term expansion, stem cells face many challenges, including limited lifespan, senescence, and loss of stemness. Therefore, a cell line capable of overcoming those problems should be built. In this study, we generated a Bmi-1-immortalized SHED cell line with an enhanced green fluorescent protein (EGFP) marker (SHED-Bmi1-EGFP) using lentiviral transduction. We compared this cell line with the original SHED for cell morphology under a microscope. The expression of Bmi-1 was detected with Western blot. Replicative lifespan determination and colony-forming efficiency assessment were using to assay proliferation capability. Senescence-associated β-galactosidase assay was performed to assay the senescence level of cells. Moreover, multipotency, karyotype, and tumour formation in nude mice of SHED and SHED-Bmi1-EGFP were also tested. Our results confirmed that Bmi-1 immortalization did not affect the main features of SHED. SHED-Bmi1-EGFP could be passaged for a long time and stably expressed EGFP. SHED-Bmi1-EGFP at a late passage showed low activity of β-galactosidase and similar multilineage differentiation as SHED at an early passage. The immortalized cells had no potential tumourigenicity ability in vivo. Moreover, we provided some suggestions for potential applications of the immortalized SHED cell line with the EGFP marker. Thus, the immortalized cell line we built can be used as a functional tool in the lab for long-term studies of SHED and stem cell-based regeneration.